Penerapan Evidence Based Practice Senam Kaki Diabetik Terhadap Penurunan Kadar Gula Darah - Mastur, Vergeina Ayu Mandalike; Pantas, Fidya Mirasari (Yayasan Syalom Cipta Sumikolah, 2025)
The general impact of uncontrolled diabetes causes serious damage to many body systems, especially the nerves and blood vessels. One way that has been proven to reduce the risk of complications in people with diabetes is good blood sugar control. Foot exercise is an activity or exercise performed by people with diabetes mellitus to prevent wounds and help smooth blood circulation in the feet. To determine the effectiveness of the application of diabetic foot exercise in people with Type II Diabetes Mellitus. The method used is a case study. The subjects used were Type II Diabetes Mellitus patients with unstable blood glucose levels. The results of the study with the application diabetic foot exercise therapy carried out for 3x 24 hours, the patient's blood sugar on the first day was 250mg/dl, and on the third day it reached 200 mg/dl, from the evaluation results it was found that diabetic foot exercise therapy was effective in lowering blood sugar in clien. The conclusion of the case study showed that blood sugar in clien. after being given diabetic foot exercise intervention, there was a decrease in blood sugar. The Suggestion to all health workers to be able to provide diabetic foot exercise therapy as a non-pharmacological therapy.